¿La era de los Códigos o la era de los Restatements? Reflexiones sobre la vigencia del Código como modelo legislativo - Vega Mere, Yuri (2020)
There are many appreciations that could be made after thirty four years of validity of a civil code. It is foreseeable and desirable that, at the end of said anniversary, different jurists and professors will deal, according to their specialties and preferences, with analyzing the different Books of the Civil Code and evaluate their benefits, deficiencies, application, modification needs, etc., without failing to mention the countless modifications it has experienced. Nor will it be strange that in any analysis, the work of the courts, the Jurisdictional Plenary of the ordinary justice or the Constitutional Court’s rulings are implied or expressly mentioned. These ones have not been scarce in civil matters, on the contrary, they have colored, transversally, the various figures traditionally born in Civil Law to be later accepted by the constitutions or reinterpreted by the Constitutional Court from constitutional texts and principles. That is not my intention. I leave the gifted and scholars in charge of those details and verses. My approach is a different one and perhaps it will be influenced by my work as a lawyer and my academic curiosity about legal experience of the United States. My curiosity, in any case, does not imply preference for any school or American legal movement in particular. I intend, in the following lines, to evaluate the validity of the Civil Code as a model and, in that order of ideas, I will try to investigate if, on the contrary, we are witnessing the era of consolidations or restatements with the definition that will be explored later on. It is clear that the starting point is the concept of a code that has been coined since the enactment of the French Civil Code in 1804.